Educational interventions as a possibility to prevent depression in the elderly in a housing project - Santos, Jovelina Fernandes dos; Andrade, Mayara Evangelista de; Souza, Joyce Wadna Rodrigues de; Barbalho, Isabela Lunara Alves; Fernandes, Petra Kelly Rabelo de Sousa; Fernandes, Marcelo Costa (Revista de Enfermagem da UFPI, 2022)
Objective: To describe educational interventions as a possibility of preventing depression in elderly people living in a housing project. Methods: The study was developed in four stages – situational diagnosis of reality; planning; implementation; and evaluation of actions carried out in 2018 –, based on the action-research method and analyzed through the methodological process of the Collective Subject Discourse. Results: After carrying out the situational diagnosis, four educational interventions were implemented. The first intervention sought to work on the construction of knowledge about depressive symptoms. The second addressed spirituality as a preventive and protective strategy. The third aimed to expose the problems faced in interpersonal relationships and the possible ways to promote help and overcome depression. The fourth intervention used art therapy as a depression prevention strategy. Conclusion: The educational interventions provided space for the participation and discussion of the elderly about depression, making them active in the learning process, which resulted in enriching meetings for the construction of individual and collective knowledge, stimulating a preventive attitude towards depression.